Peran Penyuluh Pertanian Pada Program Kredit Usaha Rakyat (KUR) Terhadap Peningkatan Pendapatan Petani Sayur Model Hidroponik Di Kabupaten Bogor - Savitri, Meytania; Sugiharjo; Winarno, Joko (CV. Multi Kreasi Media, 2023)
Agriculture is an important economic sector in Indonesia. The Central Bureau of Statistics states that this sector makes a significant contribution to the fulfillment of food needs as well as a source of income for the rural population. The agricultural sector still faces obstacles, such as low productivity and lack of access to adequate capital. One way to overcome these obstacles is to introduce modern agricultural technology, such as hydroponics. Hydroponics is a modern agricultural technology that can increase crop productivity up to two times compared to conventional farming. To overcome capital constraints, the government has launched the People's Business Credit (KUR) program. KUR aims to provide capital loans to micro, small and MSME businesses with low interest rates and long tenors. This study aims to analyze the role of extension workers in the People's Business Credit Program (KUR); analyze the factors that influence the increase in income of hydroponic model vegetable farmers; and analyze the income of hydroponic model vegetable farmers in Bogor Regency before and after the People's Business Credit Program (KUR). This method uses the basic method of quantitative research with survey techniques and sampling with Random Sampling (SRS). Bogor Regency, especially West Bogor, was chosen as the research location because West Bogor is a center for hydroponic vegetable farmers. The capital spent on hydroponic planting techniques is high compared to conventional planting techniques. In this study the sample used was 100 farmers. The analysis method used in this research is logistic regression, model feasibility, real level test, and wald test. The results showed 1) the role of extension workers in the People's Business Credit Program (KUR), 2) factors that influence the increase in income of hydroponic vegetable farmers, 3) the income of hydroponic vegetable farmers in Bogor Regency before and after the People's Business Credit Program (KUR).